RELATIONSHIP BETWEEN FAMILY FUNCTIONING AND SOCIAL SKILLS OF SENIOR SECONDARY SCHOOL STUDENTS IN NORTH-CENTRAL STATES NIGERIA - AZUA, F. H; BALARABE, M.; TUKUR , H.A.; SAMBO, AMINU (Sokoto Educational Review, 2025)
This study investigated the relationship between family functioning and social skills in senior secondary school students across four North-central states of Nigeria: Benue, Nasarawa, Niger, and Kogi. Guided by three research objectives and three hypotheses, a correlational research design was employed. The study’s population included 58,508 students, from which a sample of 394 participants was selected using a multistage sampling technique. These participants were drawn from twenty government-owned senior secondary schools, with five schools randomly chosen from each of the four states. Data were collected using two questionnaires: the Family Functioning Scale, adapted from Olson, Portner, and Bell’s FACES III, and the Social Skills Assessment Scale for Adolescents, adapted from the Children’s Services Council of Broward County. Both instruments were validated by professionals and demonstrated strong reliability, with Cronbach’s alpha values of 0.72 for both the family functioning and social skills scales. Inferential statistics were used to test the hypotheses at a 0.05 alpha level. The findings revealed a significant positive relationship between family cohesion and social skills (r=0.796,p=0.001), family adaptability and social skills (r=0.722,p=0.010), and family communication and social skills (r=0.838,p=0.001). Based on these findings, it was recommended that parents create supportive and nurturing family environments to foster social skill development. Additionally, psychologists and counselors should conduct workshops and seminars to provide resources for parents, teachers, and students to improve communication skills, which in turn promotes understanding, empathy, and conflict resolution abilities. DOI: https://doie.org/10.10318/SER.2025151597